2023
DOI: 10.3847/psj/acc844
|View full text |Cite
|
Sign up to set email alerts
|

Col-OSSOS: The Two Types of Kuiper Belt Surfaces

Abstract: The Colors of the Outer Solar System Origins Survey (Col-OSSOS) has gathered a high-quality, near-simultaneous, and brightness-complete sample of (g − r) and (r − J) colors for 102 Kuiper Belt objects (KBOs) with (u − g) and (r − z) gathered for some. We present the current state of the survey and data analysis. Recognizing that the optical colors of most icy bodies broadly follow the reddening curve, we present a new projection of the optical−near-IR (NIR) colors, which rectifies the main nonlinear features i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 69 publications
(120 reference statements)
3
34
0
Order By: Relevance
“…Previous works have shown that outer solar system color classes correlate with orbital distributions (e.g., Tegler & Romanishin 2000;Peixinho et al 2008;Tegler et al 2016;Marsset et al 2019;Ali-Dib et al 2021), which was interpreted as evidence for the existence of multiple classes of objects with distinct origins (Marsset et al 2019). This dichotomy also exists in the FaintIR/BrightIR taxonomy (Fraser et al 2023), which is explained by the fact that the BrightIR/FaintIR classification overlaps with the previously used less red/very red classification. Motivated by these earlier results, we investigate here the existence of additional correlations within the new FaintIR/BrightIR taxonomic scheme, using a combined data set of TNO color measurements from Col-OSSOS and previous observations (Section 2).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Previous works have shown that outer solar system color classes correlate with orbital distributions (e.g., Tegler & Romanishin 2000;Peixinho et al 2008;Tegler et al 2016;Marsset et al 2019;Ali-Dib et al 2021), which was interpreted as evidence for the existence of multiple classes of objects with distinct origins (Marsset et al 2019). This dichotomy also exists in the FaintIR/BrightIR taxonomy (Fraser et al 2023), which is explained by the fact that the BrightIR/FaintIR classification overlaps with the previously used less red/very red classification. Motivated by these earlier results, we investigate here the existence of additional correlations within the new FaintIR/BrightIR taxonomic scheme, using a combined data set of TNO color measurements from Col-OSSOS and previous observations (Section 2).…”
Section: Introductionmentioning
confidence: 90%
“…The observing conditions of the Col-OSSOS data set analyzed in this work are provided in Fraser et al (2023). In order to increase our sample size and strengthen any existing correlation in our data set, we combined this data set with additional, previously published measurements of similar photometric quality acquired with the Hubble Space Telescope (HST) as part of the Hubble/WFC3 Test of Surfaces in the Outer Solar System (H/WTSOSS; Fraser & Brown 2012;Fraser et al 2015).…”
Section: Sample Definitionmentioning
confidence: 99%
See 3 more Smart Citations